2009
DOI: 10.1002/nbm.1305
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of metabolic changes in the striatum of a rat model of parkinsonism: an in vivo1H MRS study

Abstract: Degeneration of the dopaminergic neurons of the substantia nigra pars compacta in Parkinson's disease induces an abnormal activation of the glutamatergic neurotransmission system within the basal ganglia network and related structures. The aim of this study was to use proton MRS to show metabolic changes in the striatum of 6-hydroxydopamine-lesioned rats, a rodent animal model of Parkinson's disease. Animals were examined before and after extensive lesioning of the nigral dopaminergic neurons and after acute a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
2
15
2
Order By: Relevance
“…In particular, in accordance with previous studies on humans [31] or on different animal models of PD [32], [33], we found a reduction of NAA/tCr. NAA is synthesized in the neuronal mitochondria and transported along axons and its concentration is reduced in case of neuronal loss [34], [35].…”
Section: Discussionsupporting
confidence: 93%
“…In particular, in accordance with previous studies on humans [31] or on different animal models of PD [32], [33], we found a reduction of NAA/tCr. NAA is synthesized in the neuronal mitochondria and transported along axons and its concentration is reduced in case of neuronal loss [34], [35].…”
Section: Discussionsupporting
confidence: 93%
“…Chassain et al reported a significant increase in Glu synthesis in the striatum of the rat after unilateral lesion of the dopaminergic nigrostriatal pathway using 13 C NMR spectroscopy [53]. However, another rat model of parkinsonism showed no significant change in Glx/tCr in the ipsi-dorsolateral striatum after 6-hydroxydopamine (6-OHDA) lesioning [28]. The discrepancies may be caused by the different dosage of 6-OHDA and different MRS methodology used.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, few in vivo 1 H-MRS studies have assessed the metabolic alterations in the canine MPTP model while most of the animal model studies for Parkinsonism induced by neurotoxin substrates were focused in small vertebrate animals like mice or rat [28][29][30][31][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations